Spatio-temporal shoreline changes analysis based on Landsat satellite images in Lahewa Beach of North Nias due to tectonics 2005. Issue 1 (September 2020) - Fauzia, A; Syamsidik, S; Syahreza, S
Abstract: The issue of accretion and erosion is one of the most comprehensive challenges in coastal morphology area. North Nias Regency is one part of Nias Island, located in the Megathrust Zone, which unfolds on Indo-Australian and Eurasian Plate subduction zones having a potential to interfere with the coastal region. Therefore, in order to detect the morphological shoreline changes, a time-efficient method of remote sensing is required. The purpose of this research is to detect the horizontal deformation of shoreline in the coastal area of North Nias Regency. This study uses Landsat 5 (TM), Landsat 7 (ETM +) and Landsat 8 (OLI) data. Also, the satellite imagery is utilized which consists of multitemporal data of pre-seismic (2000, 2003, and 2006), co-seismic (2005 and 2006), and post-seismic (2006, 2011, 2018). Furthermore, mapping and DSAS (Digital Shoreline Analysis System) methods are used. Mapping is done by digitizing the shoreline changes that occur by using the Landsat tools. On the other hand, the DSAS analysis is used to calculate and classify the area of erosion and accretion along the coast. The transect is given various colors to distinguish the shoreline alteration differences. The results show that maximum (accretion) and minimum (erosion) EPR values earned in every period in respective order are: pre-seismic with 43.540 m/yr and-80.810 m/yr, co-seismic with 600.840 m/yr and -10.590 m/yr, and post-seismic with 3.420 m/yr and -47.020 m/yr.